2020
DOI: 10.1007/s42452-020-03215-x
|View full text |Cite
|
Sign up to set email alerts
|

Saccharification and fermentation of pretreated banana leaf waste for ethanol production

Abstract: The present work reveals the potential applicability of banana leaf waste as feedstock for bioethanol production as very less work has been reported on this feedstock. For achieving the same, the performance of crude cellulases of Aspergillus niger JD-11 is explored for saccharification of untreated and pretreated (alkaline, dilute acid and steam) banana leaf waste. Therefore, to determine the best saccharifying conditions, the effects of various parameters such as enzyme loading (5-15 FPU/g), temperature (40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…In 2017, the global banana production reached a record of 114 million tons, among which China accounted for ~ 10% (~ 11 million tons per year) and ranked the second largest banana producer 13 . However, banana fruit only weights ~ 12% of the whole plant, generating huge amounts (~ 220 t/hectare) of waste residues (i.e., stems, leaves, and rachis) during production 14 . Ortiz-Ulloa et al 15 reported that the average ratio of waste residue (i.e., above-ground biomass) to product (i.e., fruit) was 3.79, and that the biomass of stems and leaves contributed 78% and 17% to the above ground biomass, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the global banana production reached a record of 114 million tons, among which China accounted for ~ 10% (~ 11 million tons per year) and ranked the second largest banana producer 13 . However, banana fruit only weights ~ 12% of the whole plant, generating huge amounts (~ 220 t/hectare) of waste residues (i.e., stems, leaves, and rachis) during production 14 . Ortiz-Ulloa et al 15 reported that the average ratio of waste residue (i.e., above-ground biomass) to product (i.e., fruit) was 3.79, and that the biomass of stems and leaves contributed 78% and 17% to the above ground biomass, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, biological pretreatment is based on fungi [21] and enzymes [22][23][24][25]. The pretreatment step usually consists of solubilizing the hemicellulose structure and reducing the lignin composition of the biomass [23,26], which facilitates enzyme access to the polymers in the enzymatic hydrolysis stage of cellulose [27,28]. Enzymes are used to reduce the complex sugars present in the biomass, thereby increasing the concentration of simple sugars, such as glucose, galactose, arabinose, and xylose.…”
Section: Introductionmentioning
confidence: 99%
“…Tarrés et al [6], obtained lignocellulosic micro/nanofibers (LCMNF) where the results determined that this biomass has the potential to be used in paper manufacturing with lower production costs and higher yields than the cellulose nanofiber (CNF) production method. Regarding bioenergy production, Suhag et al [27] reported a maximum bioethanol yield of 0.38 g/g sugar, using dried banana leaf as a carbon source. The use of banana leaf extract has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-assisted 1% NaOH pretreatment of mango peels for 2 min resulted in 0.704 g/g of reducing sugar yield where cellulose and hemicellulose were 44.2% and 26.2%, respectively [38]. Pretreatment of banana leaf in 0.1 N H 2 SO 4 at 45°C resulted in 524.483 mg/g of reduced sugar yield [39], while microwaveassisted acid pretreatment in 5% H 2 SO 4 at 180°C for 30 min resulted in the cellulose of $37% and hemicellulose of $48% from banana leaf and pith [37]. Nguyen et al did subsequent hydrothermal pretreatment at 95°C for 30 min and enzymatic hydrolysis with 2% cellulase and 0.125% Tween-20 on low-grade longan fruits wastes which yielded 240.396 g/L of reducing sugar [40].…”
Section: Fruit and Food Waste As Feedmentioning
confidence: 99%